Development of Basic Beach Volleyball Technique Training Program for Intermediate Class - Bayu Dwi Susanto; Zainal Afandi; Setyo Harmono (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
This research is motivated by the fact that there is no guidebook for bolavoli training programs that are in accordance with the characteristics of athletes, especially beach bolavoli, because the training program that is applied is still the same as indoor and outdoor bolavoli. The problem in this study is how the development and validity of the beach volleyball basic technique training program book. This research is a development research (Research and Development) with the Borg & Gall development model. The subjects of this research were beach volleyball club athletes in Tuban Regency. This research instrument uses questionnaires, interviews, observations and measurement tests. While the data analysis used is descriptive and inferential statistics. The conclusion of the results shows that the beach volleyball basic technique training program book is effective in improving the ability of athletes with the tcount value of each passing, service, smash and block test> 1.761 t table. Based on the conclusions of the results of this study, it can be an input to the coach to be able to utilize the beach volleyball basic technique training program book as an alternative media for the training process, so that the training process is more effective and interesting.